Evaluation Of Traumatic Brain Injuries Due To Alcohol Intoxication: Study In Central Hospital In West Java - Hendrikus Masang Ban Bolly; Agung Budi Sutiono; Ahmad Faried; Trajanus Laurens Yembise; Muhammad Zafrullah Arifin; Benny Atmadja Wirjomartani (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Background: Alcohol intoxication is one of the predisposing factors for the incidence of traumatic brain injury (TBI). At present, there are no hospital-based specific data that provide TBI prevalence rates due to alcohol intoxication, especially in West Java. Objective: This study aims to make descriptive observations about the incidence of TBI due to alcohol intoxication in one of the central referral hospitals in West Java. Method: A retrospective cross-sectional study was carried out involving 10,662 TBI patients recorded in the emergency department database and the Department of Neurosurgery daily case database in the period 2012 to 2018. All data relating to the two items were analyzed. Alcohol intoxication is known from a history of autoanamnesis, alloanamnesis, and the subjective identification of the examiner of alcohol odor on the breath in TBI patients who enter the emergency room. Statistical cross-tabulations were performed to present clinical and demographic phenomena in TBI cases due to alcohol intoxication. Results: The analysis showed that the prevalence of alcohol intoxication in TBI cases was 4.77% (N = 507), all of which were due to motor vehicle accidents. Mean age of 26.44 ± 9.32 years (median 24 and range 12-64). The predominant age in TBI cases due to alcohol intoxication was in the age range of 20-30 years (44.2%), and male sex 92.7%. Most cases occurred in May (12%) and on Saturdays. Based on the consciousness assessment, initial Glasgow Coma Scale in emergency department were 14 (35.9%) and classified as mild TBI (69.2%). Subarachnoid hemorrhage and cerebral contusion are predominantly lesions found on CT scans of patients (2.2%), anterior skull base fractures of 8.1%, and linear fractures (5.1%) are the dominant extracranial lesions. Soft tissue lacerations are found in 16% of all cases. Craniotomy surgery was performed in 3.6% of patients for epidural, intracerebral, and subdural hemorrhage lesion evacuation as well as correction of depressed skull fractures. About 45% were treated for a minimum of three days to observe changes in their consciousness status before discharge. Conclusion: Alcohol consumption before the head injury in motor vehicle accidents has a relationship with various complications. Alcohol intoxication is a complex issue, and more research needs to be done to create comprehensive prevention programs and regulations.